Notes on carabid beetles of the genera Coleolissus and Siopelus (Coleoptera: Carabidae: Harpalini), with description of four new species with unusual aedeagi from India and China - Kataev, Boris M. (Zootaxa, 2022)
New data on the taxonomy, morphology and distribution of several species of the genera Coleolissus Bates, 1892 and Siopelus Murray, 1859 from the southern Palaearctic and Oriental regions are provided, with special attention to the structure of their male genitalia. Coleolissus perlucens (Bates, 1878), originally described as Hypolithus perlucens Bates, 1878, the type species of Coleolissus, and C. iris Andrewes, 1924 are re-described based on the holotypes and the additional material. The following four new species with unusual aedeagi are described: C. kejvali  sp. n., C. deformipenis sp. n., and C. monstrosipenis sp. n. from Western India, and Siopelus (Neosiopelus) liangi sp. n. from Yunnan, China. The extremely unusual shape of the aedeagus of C. monstrosipenis sp. n. is discussed. It is supposed that the highly modified apical portion of the aedeagus in this species takes over some of the mechanical functions of the internal sac during mating. The following new synonyms are proposed: Coleolissus iris Andrewes, 1924 = Calathomimus splendens Ito, 1997, syn. n. = Coleolissus turturensis Ito, 2016, syn. n. The following taxa are recorded for the first time: Coleolissus iris from the Indian states of Punjab and Kerala, and the genus Siopelus (subgenus Neosiopelus Basilewsky, 1946) from China.